Cobalt containing microporous aluminohosphates as new photocatalyst for hydrogen generation under visible irradiation. (October 2018) - Hentit, H.; Boudjemaa, A.; Bouchama, A.; Jumas, J.C; Bachari, K.; Ouali, M.S
Graphical abstract: Highlights: AlPO-5 and AlPO-11, CoAlPO4-5 and CoAlPO4-11 were synthetized by hydrothermal method. Cobalt modified AlPO shows photo-catalytic activity under visible light irradiation. High activity for hydrogen evolution with CoAPO4-11photo-catalyst. High specific surface area of CoAlPO increased the (e-/h+) pairs transfer. Abstract: Novel photocatalytic materials based on cobalt type aluminophosphate molecular sieves have been elaborated by hydrothermal method. The photocatalytic activity of CoAlPO4 -5 and CoAlPO4 -11 were evaluated for hydrogen production via water reduction under visible irradiation. The synthesized materials were characterized thoroughly with respect to elemental analysis, XRD, SEM, FTIR, DR, BET and NH3 desorption measurement. Electrical conductivity, photo-electrochemical measurements were also studied. Since AlPO4 materials possess a unique chemical composition as well as structural and micro-morphological characteristics. The photocatalysts have shown a remarkable surface area ∼ 183 and 258 m 2  g −1 which lead to a better acceleration of the charge (e-/h + ) transfer by increasing the number of surface reaction sites. Under visible light, the photocatalysts exhibited a good photo-reactivity for hydrogen production with a yield of 64 and 1260 μmol g −1  min −1 for CoAlPO4 -5 and CoAlPO4 -11, respectively.